Effect of sowing density on plant growth and development of quinoa, genotype 4.5, in the brazilian savannah highlands / Efeito da densidade de semeadura no crescimento e desenvolvimento de quinoa, genótipo 4.5, no planalto central - Spehar, Juliana Evangelista da Silva Rocha, Carlos Roberto (2009)
Successful quinoa cultivation in the Brazilian Savannah (Cerrado) relies on variety adaptation to its climatic and soil conditions. Selected genotypes should be managed properly for maximal commercial yield. Experimentation in various parts of the world has been conducted to determine the population density that results best use of water light and nutrients, with ground cover during biological cycle. The species originated in the Andean Altiplano, under cold nights and low moisture availability; it spread out to valleys and only in the last decades has gained space in other environments. This experiment with genotype 4.5, possessing biological cycle of 120 days, aimed at understanding the effect of densities, varying between 100 103 to 600 1033plants ha-1, on yield and related parameters. Except for plant height, negatively associated with density increase, grain and biomass yield, harvest index and 1.000 grain weight were not affected. The probable explanation for these results is the extraordinary capacity of quinoa to compensate for missing plants, by increased vigour and branching, although number of days to maturity tends to increase.